Empirical Evaluation on Medical Image Processing in Recent Trends and Methodologies - B.Ramesh Kumar; Dr.R.Padmapriya (The Bioscan, 2025)
Medical picture handing out has advanced drastically as a consequence of recent improvements in deep neural networks, and Artificial Astuteness resolutions have been applied extensively in the healthcare industry. In order to assist medical professionals, a lot of research is being done on automated systems that can analyze photos and diagnose acute illnesses like brain tumors, bone cancer, breast cancer, bone fractures, and numerous others. This methodical investigation provides an outline of contemporary expansions in deep neural network-based medicinal imaging. Scrupulous literature analysis is followed by an overview of widely reachable information resources and recommendations for further research. Computers and other imaging technologies have successfully improved medical imaging diagnostic processes. Different medical images help with early diagnosis, describing and differentiating various health issues, which results in effective healthcare services and treatments. Medical diagnosis can be greatly aided by digital image processing and analysis, which offer the instruments required for mechanical exposure, important data extraction, and precise dimension of visual abnormality. Medical photos, however, present a number of difficulties, as do those that come up throughout the several phases of image processing. The various difficulties associated with medical imaging and medical image processing is summarized in this work. To address the need for a thorough overview of these issues, the most notable and important obstacles are listed and presented, not to deter future researchers in this area of image processing.